Computational screening and molecular dynamics reveal curcumin III and taxifolin as potential thyroid receptor modulators for hypothyroidism therapy - Oyinloye, Babatunji Emmanuel; Adewale, Adetola Ibukunoluwa; Adeyemi, Shalom Oluwafunke; Fajana, Omotola Martha; Olusola, Olutosin Samuel; Oyinloye, Oluwatoyin Mary; Ayeni, Aderonke Moyosola; Akawa, Ayodeji Benjamin; Idowu, Olajumoke Tolulope; Ibikunle, Austine Idowu; Olojo, Folake Olayinka; Ajiboye, Basiru Olaitan (Frontiers in Endocrinology, 2026)
Hypothyroidism is a condition marked by inadequate thyroid hormone production. It is typically treated with Levothyroxine, which, despite its effectiveness, can cause adverse effects on metabolism and the cardiovascular system. In this study, an in silico approach was used to screen phytochemicals from Curcuma longa, Moringa oleifera, and Nigella sativa for their potential to activate the thyroid receptor. A total of 439 compounds were docked against Thyroid Receptor Beta 1 (TRβ1) and Thyrotropin-Releasing Hormone Receptor (TRHR) using AutoDock Vina. Among them, valoneic acid dilactone, curcumin III, taxifolin, luteolin, lophenol, and stigmastanol were identified from the three plants as performing better than others. These compounds were further evaluated with ADMET predictions and molecular dynamics simulations to assess their drug-like properties and stability. Lophenol from Nigella sativa showed the highest binding affinity to TRβ1 (-13.62 kcal/mol) with an inhibition constant of 0.1037 nM, surpassing levothyroxine (-11.60 kcal/mol and 6.63 nM). Also, stigmastanol from Nigella sativa showed the highest binding affinity to TRHR (-8.71 kcal/mol) with an inhibition constant of 415 nM, surpassing levothyroxine (-7.64 kcal/mol and 2530 nM). However, the two compounds exhibited some unfavourable ADMET properties that could be improved through formulation science. Curcumin III and taxifolin demonstrated favourable ADMET properties, including optimal solubility, lipophilicity, and polar surface area, suggesting good oral bioavailability. Molecular dynamics simulations were carried out using Desmond. The results revealed that curcumin III, lophenol, and taxifolin maintained strong stability, with RMSD values of 1.70 ± 0.005 Å, 2.17 ± 0.012 Å, and 2.50 ± 0.014 Å, respectively, for TRβ1, and RMSD values of 3.82 ± 0.014 Å, 4.29 ± 0.019 Å, and 3.31 ± 0.017 Å, respectively, for TRHR. This study identified Curcumin III from Curcuma longa and taxifolin from Moringa oleifera as promising natural compounds for the treatment of hypothyroidism. Further validation through in vitro, in vivo, and ex vivo studies is recommended.